Possibilities of transcranial direct current stimulation (tDCS) use in elite sport - S. I. Barshak; M. D. Didur; V. V. Zavyalov; O. V. Kara; I. N. Mitin; K. S. Nazarov; M. G. Ogannisyan (National Electronic Information Consortium (NEICON), 2021)
Transcranial direct current stimulation has proven to be the method that can modulate neural activity in various cases. As this method has been shown to be effective in improving muscular strength, reaction time and accuracy, motor learning, it seems to be promising in elite sports.This paper provides an overview of studies on tDCS and its impact on central nervous system functioning, with an emphasis on potential sports utility. This review demonstrates that the basic mechanism of the effect of tDCS on nervous system functioning is its ability to modulate the excitability of neurons.tDCS is able to influence various components of electrocortical potentials, the amplitude of the motor evoked potential, as well as the mechanisms of long-term potentiation and, as a consequence, the cellular mechanisms of motor learning and neuroplasticity in general. The beneficial effect of tDCS on attention selectivity and signal detection has been noted. It is also shown that tDCS can accelerate learning and enhance performance in a range of complex cognitive tasks.In addition, a number of studies showing that tDCS can increase the efficiency of performing arithmetic and problem solving tasks are considered.In the context of sports, the influence of tDCS over motor areas on motor learning and on the accuracy of voluntary movements seems to be important. Its ability to influence speed and strength indicators, namely, the maximum isometric force of various muscle groups and explosive strength, as well as endurance indicators seems promising, too. The review also shows that tDCS is reasonably safe and that serious adverse effects are extremely rare; the most common adverse effect is local skin irritation due to poor electrode placement.